EFFECT OF CYTOJEEP AND FLORIN FOLIAR APPLICATION ON GROWTH AND FLOWERING OF PANSY (VIOLA TEICOLOR) - M. Sadiq, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was conducted in the lathhouse of the Department of Horticulture and Landscape Gardening, College of Agriculture, University of Baghdad to study the effect of two nutrition compounds called Cytojeep and Florin on the vegetative and flowering characters of Pansy (Viola tricolor) during the fall season of 2016. Plants were planted in 20 cm/diameter pots and sprayed two times with different concentrations of Cytojeep 0, 0.5, and 1 ml.L-1 and Florin 0, 0.15, and 0.30 ml.L-1 started after one month of planting with 21 days intervals. The results were as follows: Spraying with Cytojeep resulted in improving all vegetative and flowering traits under investigation. The foliar application of Cytojeep at 1 ml.L-1significantly increased plant height 13.84 cm, number of branches per plant 7.40, fresh weight 4.98 g, dry weight 0.88, flowering time 47 days, flower diameter 74.99 mm, number of flowers 5.97. Moreover, spraying with Florin at 0.30 ml.L-1 significantly increased all vegetative and flowering characteristics in terms of plant height 14.01 cm, number of branches per plant 7.42, fresh weight 5.03 g, dry weight 0.91 g flowering time 47 days, flower diameter 75.70 cm, number of flowers 5.87. Finally, the interaction between the two nutrition compounds showed to have an effect on all vegetative and flowering traits under investigation where the highest concentration of Cytojeep and Florin gave the most significant results in plant height 15.67 cm, number of branches per plant 7.89, fresh weight 5.76 g, dry weight 1.18 g, flowering time after 43 days, flower diameter 81.66 mm, number of flowers 6.85.